Объяснение:
1)
а=1; b=7; c= -18
[tex]x = \frac{ - 7 + \sqrt{7 {}^{2} - 4 \times 1 \times ( - 18) } }{2 \times 1} [/tex]
[tex]x = \frac{ - 7 + \sqrt{121} }{2} [/tex]
[tex]x = \frac{ - 7 + 11}{2} [/tex]
[tex]x = \frac{ - 7 - \\ 11}{2} [/tex]
х=2;
х=-9
2)
а= 1; b=-1; c= -42
[tex]x = \frac{ - ( - 1) + \sqrt{( - 1) {}^{2} - 4 \times 1 \times ( - 42) } }{2 \times 1} [/tex]
[tex]x = \frac{1 + \sqrt{1 + 168} }{2} [/tex]
[tex]x = \frac{ 1 + \sqrt{169} }{2} [/tex]
[tex]x = \frac{1 + 13}{2} [/tex]
[tex]x = \frac{1 - 13}{2} [/tex]
х=7
х= -6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
1)
а=1; b=7; c= -18
[tex]x = \frac{ - 7 + \sqrt{7 {}^{2} - 4 \times 1 \times ( - 18) } }{2 \times 1} [/tex]
[tex]x = \frac{ - 7 + \sqrt{121} }{2} [/tex]
[tex]x = \frac{ - 7 + 11}{2} [/tex]
[tex]x = \frac{ - 7 - \\ 11}{2} [/tex]
х=2;
х=-9
2)
а= 1; b=-1; c= -42
[tex]x = \frac{ - ( - 1) + \sqrt{( - 1) {}^{2} - 4 \times 1 \times ( - 42) } }{2 \times 1} [/tex]
[tex]x = \frac{1 + \sqrt{1 + 168} }{2} [/tex]
[tex]x = \frac{ 1 + \sqrt{169} }{2} [/tex]
[tex]x = \frac{1 + 13}{2} [/tex]
[tex]x = \frac{1 + 13}{2} [/tex]
[tex]x = \frac{1 - 13}{2} [/tex]
х=7
х= -6